Ndj1, a telomere-associated protein, regulates centrosome separation in budding yeast meiosis - Li, Ping (J Cell Biol, 2015)
Yeast centrosomes (called spindle pole bodies [SPBs]) remain cohesive for hours during meiotic G2 when recombination takes place. In contrast, SPBs separate within minutes after duplication in vegetative cells. We report here that Ndj1, a previously known meiosis-specific telomere-associated protein, is required for protecting SPB cohesion. Ndj1 localizes to the SPB but dissociates from it ∼16 min before SPB separation. Without Ndj1, meiotic SPBs lost cohesion prematurely, whereas overproduction of Ndj1 delayed SPB separation. When produced ectopically in vegetative cells, Ndj1 caused SPB separation defects and cell lethality. Localization of Ndj1 to the SPB depended on the SUN domain protein Mps3, and removal of the N terminus of Mps3 allowed SPB separation and suppressed the lethality of NDJ1-expressing vegetative cells. Finally, we show that Ndj1 forms oligomeric complexes with Mps3, and that the Polo-like kinase Cdc5 regulates Ndj1 protein stability and SPB separation. These findings reveal the underlying mechanism that coordinates yeast centrosome dynamics with meiotic telomere movement and cell cycle progression.